Bridging Worlds Through Comparative Literature - Kasimov Abdugapir Abdikarimovich (Indonesian Journal of Cultural and Community Development, 2024)
This study emphasizes the critical role of comparative literary studies in understanding the modern literary process. Traditional literary analyses often overlook the rich intercultural dynamics that comparative studies highlight. Our research aims to bridge this gap by developing a theoretical framework that comprehends literary aesthetics in a globalized context through a qualitative analysis of diverse literary texts. Initial findings reveal that such a comparative approach not only deepens our understanding of universal literary themes but also enhances the appreciation of diverse cultural expressions. This work underscores the importance of integrating comparative literary studies into mainstream literary education to foster a more inclusive understanding of global literary phenomena. Highlights: Illuminates universal themes across cultures Develops new comparative literary framework Advocates comparative studies in education Keywords: Comparative Literature, Global Literary Dynamics, Contact Genetic Comparison, Aesthetic Analysis, Cultural Expressions.